Peran Tokoh Agama Dalam Menjaga Keharmonisan Masyarakat Pasca Pemilihan Umum Di Kabupaten Pasuruan - Khadavi, Muhammad Jadid; Gafur, Abd; Anam, Rifki Khairul (Universitas Muhammadiyah Tangerang, 2024)
This research aims to reveal and analyze the role of religious leaders in maintaining harmony in society after the 2024 election. This research highlights the urgency of collaboration between religious leaders, community leaders and village governments in preventing polarization of society after the 2024 election through open and inclusive dialogue spaces. This research method uses a qualitative approach and the type of research is a case study. The data collection process was obtained through observation of community behavior and in-depth interviews with religious leaders, community leaders, village government and residents. Research findings show that religious leaders in Wonokoyo Village, Beji District, Pasuruan Regency have a significant role in building understanding among the community after the 2024 election about the importance of maintaining the values of unity, tolerance and justice. The strategy used by religious leaders is uswah hasanah and sustainable moral development. Communication between religious leaders, community leaders and village government must also run synergistically. Therefore, the results of this research can be a basis for developing policies that support efforts to prevent societal polarization which can threaten stability and create disharmonious situations